Temperature dependence of interaction parameters in electrolyte NRTL model. Issue 4 (7th November 2015) - Hossain, Nazir; Bhattacharia, Sanjoy K.; Chen, Chau‐Chyun
Abstract : The electrolyte NRTL model captures the electrolyte solution nonideality over the entire concentration range with two binary interaction parameters. Here, the temperature dependence of the binary parameters is formulated with a Gibbs‐Helmholtz expression containing three temperature coefficients associated with Gibbs energy, enthalpy, and heat capacity contributions. We show the Gibbs energy term is correlated to the excess Gibbs energy of aqueous single electrolyte systems at 298.15 K. With the Gibbs energy term identified, the enthalpy term is correlated to the excess enthalpy at 298.15 K. With the Gibbs energy term and the enthalpy term identified, the heat capacity term is correlated to the excess heat capacity at 298.15 K. Once the temperature coefficients are properly quantified by regressing data of mean ionic activity coefficient, excess enthalpy, and heat capacity at 298.15 K or the equivalents, the model provides a comprehensive thermodynamic framework to represent all thermodynamic properties of electrolyte solutions. © 2015 American Institute of Chemical Engineers AIChE J, 62: 1244–1253, 2016